IMPLEMENTASI VIRTUAL FITTING BERBASIS POLA DIGITAL UNTUK MENDUKUNG PEMBELAJARAN TATA BUSANA BERKELANJUTAN DI SMK - Dermawan; Ulfa Annida Damanik; Titen Darlis Santi; Winda Bali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The demands of the workplace increasingly require human resources proficient in digital technology, including in the fashion industry. This situation aligns with the goals of vocational high schools (SMK) vocational education, which is oriented towards preparing competent, work-ready graduates according to industry needs. The purpose of this research is to improve the effectiveness of digital pattern learning that aligns with industry needs and enhance student skills through the development of innovative learning media that support teachers and students in achieving digitalization competency in digital pattern-based Virtual Fitting.The research method used was Research and Development (R&D) with the Four-D development model. The research subjects were 11th-grade Fashion Design students at Citra Harapan Private Vocational High School. The stages included the define stage to identify learning needs, the design stage to design digital learning media appropriate to the curriculum and student characteristics, the develop stage to develop digital-based learning media, and the disseminate stage to conduct limited trials and refinements based on feedback.The results of the development research were as follows: the analysis of student needs revealed that 54.8% needed digital pattern-based Virtual Fitting learning materials, with a rating of 0.88 for the material and 0.87 for the material's suitability. Based on the responses of lecturers, teachers, and students, the Virtual Fitting teaching material based on digital patterns was declared very practical. The Virtual Fitting teaching material based on digital patterns was declared effective in improving students' pattern-making skills by 15.7%. Based on the results of this study, it can be concluded that learning using the Virtual Fitting teaching material based on digital patterns is significantly effective in improving students' higher-order thinking skills and learning outcomes in pattern-making.